2008
DOI: 10.1080/02763890802097144
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Use of Gerotechnology: Implications for Aging in Place

Abstract: ABSTRACT.Understanding perceptions and use of gerotechnology is crucial to optimize design, application, and education strategies that may reduce caregiver burden, extend healthy aging in place, and minimize demands on the health care system. A pilot project was conducted to explore attitudes, opinions, and preferences of older adults concerning the use of technology to support and extend their ability to "aging in place." Four major themes emerged as important for older adults to age in place: safety and inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 26 publications
4
41
1
6
Order By: Relevance
“…The results showing BIU for the VOTA system align closely with published results showing positive feelings with the virtual practice of IADLs (Kizony et al, 2012;Ruparel et al, 2009;Yamaguchi et al, 2012). The strong correlation found between PU and BIU is consistent with the TAM (Davis, 1989) and with previous observations on the importance of PU for acceptance of technology (Mahmood et al, 2008). Likewise, the strong correlation found between attitude and BIU supports Davis's (1989) supposition that people's intention to perform certain behaviors is linked to positive feeling or emotion.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results showing BIU for the VOTA system align closely with published results showing positive feelings with the virtual practice of IADLs (Kizony et al, 2012;Ruparel et al, 2009;Yamaguchi et al, 2012). The strong correlation found between PU and BIU is consistent with the TAM (Davis, 1989) and with previous observations on the importance of PU for acceptance of technology (Mahmood et al, 2008). Likewise, the strong correlation found between attitude and BIU supports Davis's (1989) supposition that people's intention to perform certain behaviors is linked to positive feeling or emotion.…”
Section: Discussionsupporting
confidence: 82%
“…Two other important factors in determining acceptance are perceived usefulness (PU) and perceived ease of use (PEOU; McCreadie & Tinker, 2005). With respect to PU, research has suggested that older adults accept new technology if they believe it might improve their quality of life and independence (Mahmood, Yamamoto, Lee, & Steggell, 2008;Steele, Lo, Secombe, & Wong, 2009). Regarding PEOU, older adults accept technology more readily if it incorporates simple interfaces that are easy to understand (Gell et al, 2013).…”
mentioning
confidence: 99%
“…Even the still healthy and active older adults might need some form of assistance in the near future [5,18]. Informal family caregivers often provide assistance, but caring for a family member can be stressful and overwhelming [11,22,24]. AAL technologies offer a promising perspective on aging in place.…”
Section: Background and Problem Statementmentioning
confidence: 98%
“…emergency button), and are therefore easy to use and flexible to the individual context of the user [10]. For example, through unobtrusive sensors the older person's activity level can be monitored, thereby allowing the caregivers to detect emergency situations and recognize functional decline at an early stage [11,20]. Despite the fact that AAL technologies have a great potential to facilitate independent living and reduce the burden on caregivers and health care budgets, the likelihood of adoption of those technologies remains uncertain [7].…”
Section: Background and Problem Statementmentioning
confidence: 99%
“…The third, disability or institutional migration is taken when individuals are living with severe disability or poor health requiring assisted living in an institution (Speare et al 1991) (see, for Canadian examples, Carriere and Pelletier 1995;Everitt and Gfellner 1996). However, housing modifications, housing satisfaction or gerotechnology may increase inertia of older individuals, as these may assist with accommodating reduced capacities (Erickson et al 2006;Golant and LaGreca 1994;Mahmood et al 2008;Oswald et al 2007).…”
Section: Introductionmentioning
confidence: 97%